2009
DOI: 10.1093/bja/aep293
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant activated factor VII for a patient with factor VII deficiency undergoing urgent intracerebral haematoma evacuation with underlying cavernous angioma

Abstract: Inherited factor VII (FVII) deficiency is a rare autosomal-recessive bleeding disorder. There are no clear guidelines regarding therapy in such patients when intracerebral surgery is performed. We report the use of recombinant activated FVII (rFVIIa) for the prophylaxis of bleeding in a female with FVII deficiency (8% of activity) undergoing urgent removal of a right fronto-rolandic intracerebral haematoma secondary to a bleeding from a cavernous angioma. To assist haemostasis during and after surgery, rFVIIa … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 14 publications
0
4
0
1
Order By: Relevance
“…A large number of different F7 gene variants, including missense, nonsense, promoter and splice site mutations, have been reported. In addition, the functional impact of certain variants has been investigated in order to provide evidence for the underlying molecular mechanisms of FVII deficiency (8,9).…”
Section: Introductionmentioning
confidence: 99%
“…A large number of different F7 gene variants, including missense, nonsense, promoter and splice site mutations, have been reported. In addition, the functional impact of certain variants has been investigated in order to provide evidence for the underlying molecular mechanisms of FVII deficiency (8,9).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, in a study by Diprose et al [16] assessing the effect of activated recombinant factor VII in non coronary cardiac surgery and the need of transfusion after the cardiopulmonary bypass, the authors concluded that administrating recombinant factor VII was beneficial and reduced the need for blood transfusion in such patients without causing any side effects. Moreover, Liu and colleagues [17] studied the value of recombinant factor VII in patients for intracerebral hematoma drainage having factor VII deficiency and found out that its use was effective in emergency neurosurgery. On the contrary, in a study by Bowels and colleagues [18] for predicting the response of non-hemophilic patients with bleeding to activated recombinant factor VII, they showed that only eight patients responded to an early single dose of factor VII who had good prognosis while patients with poor prognosis showed no response suggesting that its efficacy depending on the time of administration that may affect the prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…In the past, plasma-based therapies such as fresh frozen plasma, plasma-derived FVII concentrates or prothrombin complex concentrates were the available treatment options for patients with FVII deficiency [10]. Currently, the most commonly administered treatment option is recombinant activated FVII (rFVIIa) (NovoSeven1, Novo Nordisk A/S, Bagsvaerd, Denmark) [6], which is indicated in Japan for the treatment of bleeding and for the prevention of bleeding during surgery/invasive procedures in patients with congenital FVII deficiency [11].…”
Section: Introductionmentioning
confidence: 99%